DISCOVERING THE MEANING OF VERBAL AND VISUAL SIGNS IN L’OREAL PARIS VIDEO ADVERTISEMENT: A SEMIOTIC STUDY - Andina, A.A. Diah Trisna; Pratiwi, Desak Putu Eka; Utami, Ni Made Verayanti (Institut Pariwisata dan Bisnis Internasional, 2021)
The study entitled “Discovering the Meaning of Verbal and Visual Signs in L’Oreal Paris Video Advertisement: A Semiotic Study” which aimed to identify and analyze the verbal and visual signs as well as their meaning. Commercial advertisement plays an important role in promoting a new product. It could be the fastest and practical ways to sell the products or services to the costumers. The data was taken from L’Oreal Paris Total Repair 5 Shampoo video advertisement. The data was collected by observation method and analyzed in descriptive qualitative method. This research used three theories, they are of semiotic theory by Saussure (1983: 67), theory of meaning by Barthes (1977) and theory of color terms by Wierzbicka (1996). The findings showed that there are 5 verbal signs and 6 visual signs. As the result of this study, the verbal signs in this advertisement are appeared as the texts and sentences that written in big font texts, while the visual signs appeared as a picture and also supported by some colors which could attract the audience’s attention when they watch the advertisement video. Both of verbal and visual signs convey denotative and connotative meaning.